PENGARUH VARIASI UNSUR AL DAN NB TERHADAP DESAIN PADUAN TI-AL-NB DENGAN SIMULASI MOLECULAR DYNAMIC UNTUK APLIKASI BIOMEDIS - Rosyid Ridho, Muhammad
Titanium and its alloys are often used for biomaterials because it has good combination of mechanical properties and biocompatibility, and also economical in terms of price. Ti-6Al-4V extra low interstity (ELI) is often used for biomaterials, it has good strength and is widely used, but vanadium has a relatively high level of toxicity, so vanadium will be replaced by niobium that has a lower level of toxicity. Ti-Al-Nb that has been standardized for implant raw materials is Ti-6Al-7Nb, so in this study it will be seen how the influence of Al and Nb with the variation around the composition of Ti-6Al-7Nb. Conventional metal alloy designs need long time and big cost, so that by conducting molecular dynamic simulations, the predictions obtained from mechanical properties are faster and cheaper as well as with a large number of atom with variant temperatures.